2014
DOI: 10.1038/nature13582
|View full text |Cite
|
Sign up to set email alerts
|

Stochasticity of metabolism and growth at the single-cell level

Abstract: Elucidating the role of molecular stochasticity in cellular growth is central to understanding phenotypic heterogeneity and the stability of cellular proliferation. The inherent stochasticity of metabolic reaction events should have negligible effect, because of averaging over the many reaction events contributing to growth. Indeed, metabolism and growth are often considered to be constant for fixed conditions. Stochastic fluctuations in the expression level of metabolic enzymes could produce variations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
480
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 388 publications
(515 citation statements)
references
References 29 publications
21
480
0
2
Order By: Relevance
“…Tumor heterogeneity may contribute to tumor aggression, invasion, metastases, and therapy resistance [1][2][3]. Studies of tumor heterogeneity are challenging because traditional cell and tissue analyses require pooling of proteins, RNA, or DNA from hundreds to thousands of cells, which provides information on the protein and genetic expression of the majority of cells but may mask unique expression profiles and phenotypes of heterogeneous populations.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor heterogeneity may contribute to tumor aggression, invasion, metastases, and therapy resistance [1][2][3]. Studies of tumor heterogeneity are challenging because traditional cell and tissue analyses require pooling of proteins, RNA, or DNA from hundreds to thousands of cells, which provides information on the protein and genetic expression of the majority of cells but may mask unique expression profiles and phenotypes of heterogeneous populations.…”
Section: Introductionmentioning
confidence: 99%
“…Quantifier les fluctuations à l'échelle de la cellule unique Nous avons combiné microscopie en time-lapse, analyse d'image de cellules uniques, analyse statistique et modé-lisation mathématique pour montrer comment et à quel point les fluctuations d'expression des gènes peuvent affecter la croissance de bactéries Escherichia coli [5]. La microscopie time-lapse consiste simplement à capturer des images de colonies de bactéries à des intervalles de temps réguliers.…”
Section: Fluctuations D'origine Thermique à L'échelle Cellulaireunclassified
“…In the third talk of this section, Dr. Sander Tans (FOM Institute AMOLF, Netherlands) showed their recent results in elucidating the role of molecular stochasticity in cellular growth [8]. Using time-lapse microscopy, he demonstrated that expression fluctuations of catabolically active enzymes can propagate and cause growth fluctuations, with transmission depending on the limitation of the enzyme to growth.…”
Section: From Molecules To Cellular Behaviormentioning
confidence: 99%